VEGETATION PERIOD OF MEDICINAL AMARANTH PLANT MORPHOBIOLOGICAL INDICATORS (British Journal of Global Ecology and Sustainable Development, 2023)
This article analyzes the morphobiological indicators of the amaranth plant, which is widely used in scientific medicine, during the vegetation period.